Unequal freedom: how race and gender shaped American citizenship and labor - Glenn, Evelyn Nakano (Harvard University Press, 2002)
The inequalities that persist in America have deep historical roots. Evelyn Nakano Glenn untangles this complex history in a unique comparative regional study from the end of Reconstruction to the eve of World War II. During this era the country experienced enormous social and economic changes with the abolition of slavery, rapid territorial expansion, and massive immigration, and struggled over the meaning of free labor and the essence of citizenship as people who previously had been excluded sought the promise of economic freedom and full political rights.After a lucid overview of the concepts of the free worker and the independent citizen at the national level, Glenn vividly details how race and gender issues framed the struggle over labor and citizenship rights at the local level between blacks and whites in the South, Mexicans and Anglos in the Southwest, and Asians and haoles (the white planter class) in Hawaii. She illuminates the complex interplay of local and national forces in American society and provides a dynamic view of how labor and citizenship were defined, enforced, and contested in a formative era for white-nonwhite relations in America.
Keywords: 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; amériques; approches et analyses; cours; discipline; droits des femmes*; droits des personnes; histoire et politique; intersectionnalité; inégalités; pol4212; premier cycle; périodes historiques; racisme; racisme systémique; régions géographiques; sexisme; systèmes d'oppressions; thématiques; états-unis; études critiques de la race; études de genres

L'énigme de l'égalité - Scott, Joan Wallach (Cahiers du Genre, 2002)
Il arrive fréquemment que les débats sur l’action positive aux États-Unis traitent séparément les questions relatives à l’égalité et à la différence, aux droits individuels et aux identités de groupe. Pourtant, ce sont là des couples de concepts interdépendants, chacun étant lié à l’autre dans une tension nécessaire. Les tensions se manifestent de façon spécifique selon la période historique et doivent être analysées en fonction du contexte politique qui les porte et non comme des choix moraux ou éthiques a-historiques. Cet essai explore trois paradoxes — qui sont des tensions insolubles — propres aux débats sur l’action positive : 1) l’égalité est un principe absolu et une pratique historique contingente ; 2) les identités de groupe définissent des individus et leur refusent la pleine expression ou réalisation de leur individualité ; 3) les revendications de l’égalité impliquent l’acceptation et le rejet de l’identité de groupe produit par la discrimination. Autrement dit, les termes de l’exclusion, qui fondent la discrimination, sont à la fois refusés et reproduits dans la demande d’inclusion.
Keywords: action positive; amériques; approches et analyses; cours; discipline; droits des femmes*; europe; france; histoire; histoire et politique; intersectionnalité; inégalités; philosophie; pol4102; premier cycle; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis